The Philosophy of Color in Malay Tradition Symbolism, and the Implementation of Cultural Values for Modern Society - Hasnah Faizah; Irwanto Irwanto; Ika Apriyanti; Putri Endang Kemalasari; Hendri Ramadhan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to comprehensively examine the profound philosophical values and moral messages deeply embedded within the traditional color conventions of Malay customs. The primary focus is to critically analyze the historical and contemporary use of color as a powerful